Analisis SWOT InsurTech Produk Wakaf Asuransi Syariah - Ainul Yakin, Ikin; Irawan, Wahri; Rahmawati, Ria (Syar'Insurance: Jurnal Asuransi Syariah, 2024)
Insurance companies in Indonesia, especially sharia insurance, are currently increasingly developing with various strategies. One strategy is through an InsurTech approach to sharia insurance waqf products that will be offered to the public. Based on the background above, how to analyze the strengths, weaknesses, opportunities and threats of InsurTech Sharia Insurance Waqf Products at PT Asuransi Jiwa Bersama Bumi Putera 1912 Branch Cilegon Prov. Banten. This research aims to analyze the strengths, weaknesses, opportunities and threats of InsurTech Sharia Insurance Waqf Products at PT Asuransi Jiwa Bersama Bumi Putera 1912 Cilegon Branch, Banten Province. This type of research is field case study research with a descriptive qualitative approach. Data collection was carried out using interviews, observation and documentation methods. The primary data source in this research comes from interviews with stakeholders. Meanwhile, secondary data in this research comes from books, several journals and the company's official website. Based on the results of the analysis that has been carried out, it is known that the condition of the Bumi Putera Muda 1912 Cilegon Branch is in an unfavorable position. However, there are several strategies that can be an alternative choice for companies in developing digital technology. Among them are: First, the SO (Strength Opportunity) Strategy, such as creating various contemporary innovations in modern applications in order to attract digital markets and collaboration.